Trajetória da capacidade para o trabalho em trabalhadores brasileiros no contexto da pandemia de COVID-19 - Scribone, Letícia Figueiredo (Universidade Federal de São Carlos, 2025)
Introduction: The COVID-19 pandemic has had immediate and delayed effects on workers. The sudden change in working relationships may have impacted their ability to work. Objective: To describe the ability to work over time, through trajectory analysis, in Brazilian workers during the COVID-19 pandemic. The study hypothesis is that it will be possible to identify different trajectories of work capacity. Methods: This is a longitudinal study with Brazilian workers who responded to the Work Capacity Index (WCI) in 2020, 2021, 2022, and 2023 via an electronic form. Trajectory analysis was performed using latent class growth analysis to identify different work capacity trajectories over time. Results: Three different work capacity trajectories over time were identified during the COVID-19 pandemic in Brazilian workers, all with stable patterns over the years and different levels of capacity: trajectory 1. low to moderate, trajectory 2. good, and trajectory 3. excellent work capacity. Conclusion: The results obtained show that there are three different trajectories of work capacity in Brazilian workers assessed in the context of the COVID-19 pandemic, all of which show a stable pattern over time.
Trajectory of work capacity among brazilian workers in the context of the COVID-19 pandemic
Keywords: Capacidade para o trabalho; Pandemia; Coronavírus; OUTROS; 3. Saúde e Bem-Estar